2013
DOI: 10.1103/physrevlett.110.067202
|View full text |Cite
|
Sign up to set email alerts
|

Full Electric Control of Exchange Bias

Abstract: We report the creation of a multiferroic field effect device with a BiFeO(3) (BFO) (antiferromagnetic-ferroelectric) gate dielectric and a La(0.7)Sr(0.3)MnO(3) (LSMO) (ferromagnetic) conducting channel that exhibits direct, bipolar electrical control of exchange bias. We show that exchange bias is reversibly switched between two stable states with opposite exchange bias polarities upon ferroelectric poling of the BFO. No field cooling, temperature cycling, or additional applied magnetic or electric field beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
202
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(210 citation statements)
references
References 22 publications
7
202
0
Order By: Relevance
“…This state displays an exchange-bias field and magnetotransport that can be tuned by switching the FE polarization, increasing the potential for device control through interfacial coupling. However, a complete picture of the interplay between FM and AFM orders in this heterostructure has yet to be reached.Current understanding of the exchange-bias field, which arises from the interaction between FM and G-type AFM [AFMðGÞ] orders at the interface, is based on spin canting or pinning in BFO, with the assumption of negligible canting in the manganite layer [14][15][16]. However, given that the spin interaction is mutual, it is not clear why FM spins in LSMO can induce AFM spins in BFO to cant, but the reverse has not been discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This state displays an exchange-bias field and magnetotransport that can be tuned by switching the FE polarization, increasing the potential for device control through interfacial coupling. However, a complete picture of the interplay between FM and AFM orders in this heterostructure has yet to be reached.Current understanding of the exchange-bias field, which arises from the interaction between FM and G-type AFM [AFMðGÞ] orders at the interface, is based on spin canting or pinning in BFO, with the assumption of negligible canting in the manganite layer [14][15][16]. However, given that the spin interaction is mutual, it is not clear why FM spins in LSMO can induce AFM spins in BFO to cant, but the reverse has not been discussed.…”
mentioning
confidence: 99%
“…The combination of these materials thus has great potential for exhibiting novel phenomena by coupling different FM, AFM, and FE phases across the interface. Indeed, a new interfacial state between LSMO and BFO has been discovered experimentally and discussed theoretically [2,[14][15][16]. This state displays an exchange-bias field and magnetotransport that can be tuned by switching the FE polarization, increasing the potential for device control through interfacial coupling.…”
mentioning
confidence: 99%
“…In rhombohedral Pb(Mg 1/3 Nb 2/3 ) 0. 72 Ti 0.28 O 3 (PMN-PT) single crystals with high piezoelectricity, Thiele et al [27] discovered that the T c of LSMO thin film increased by 19 K and the ME coefficient was about 6×10 −8 s m −1 , which further confirmed the effective contribution from the strain transfer across the interface on the ME coupling. In principle, mechanical-stress-controlled Mn-O bond length can be assumed as the microscopic origin of the ferromagnetic states of the LSMO thin film.…”
Section: Strain Effectsmentioning
confidence: 61%
“…More importantly, the interfacial exchange bias can be controlled by switching the ferroelectric polarization of the multiferroic BFO. In such a heterostructure, Wu et al [71,72] demonstrated that the ferroelectric polarization could be coupled with the ferromagnetic order at BFO interface, which was used to control the magnitude of magnetic coercive field and the directions of the exchange bias as shown in Fig. 6.…”
Section: Science China Materialsmentioning
confidence: 99%
“…Nowadays, they find numerous applications in magnetic storage devices, sensors and also in spintronics [1][2][3][4][5][6][7]. Nevertheless, basic phenomena are not understood so far and are still a matter of research [8][9][10][11].…”
mentioning
confidence: 99%